The Influence of Interest and Creativity on Learning Achievement Students of SMKN 1 Tongkuno - Usman Usman; Badiun Badiun; Nontje Sangi (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to: (1) determine the effect of interest in learning on student achievement in the electrical installation engineering expertise program 11th class SMK Negeri 1 Tongkuno, and (2)To determine the effect of learning creativity on student achievement in the electrical installation engineering skill program 11th class SMK Negeri 1 Tongkuno, (3) To determine the effect of interest and creativity on student achievement in the electrical installation engineering expertise program 11th class SMK Negeri 1 Tongkuno. The population in this study was all students of class XI-a (28 students) and students of class XI-b (25 students) at SMK Negeri 1 Tongkuno, with 53 students, so this research is a population study. Questionnaires and documentation do data collection. Questionnaire to collect data on interest and creativity in learning while documentation to collect data on learning achievement. This instrument trial was conducted on 35 students of 11th class TITL SMK Negeri 1 Tongkuno; the multiple regression analysis techniques were used in the data analysis. The analysis requirements test was conducted before data analysis, including normality, multicollinearity, autocorrelation, and heteroscedasticity. The result of this study is that (1) learning interest (X1) has a significant effect on learning achievement (Y), which is indicated by a significance value of .000 < .023 so that the first hypothesis proposed can be accepted. Learning creativity (X2) has a significant effect on student achievement (Y); this is indicated by a significance value of .004 < .05, so the second hypothesis formulated in this study can be accepted. Based on the result of hypothesis testing, it claims that student progress in the electrical installation engineering competence program 11th class SMK Negeri 1 Tongkuno is significantly influenced by enthusiasm and creativity, it can be proven by the significance value of F (F-sig) of = .000 which means it is smaller than α = .05 (F-sig .000 < .05).